2017
DOI: 10.1055/s-0043-121568
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal Abdominal Diameter does not Predict Metabolic Traits Better than Waist Circumference-Related Measures of Abdominal Obesity in Obese Subjects

Abstract: Data show various associations between anthropometric measures of abdominal obesity and metabolic traits in obese women but overall much less in obese men. Most metabolic traits are better predicted by WC than by SAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Among many of the mechanisms of abdominal obesity, chronic inflammation, cell apoptosis, energy imbalance, and gut microbial enterotypes can result in an excessive accumulation of adipose tissue. [ 35 , 36 ] It is possible that moxibustion treatments could lead to the inhibition of inflammatory, promotion of energy metabolism, and reduction of pro-inflammatory cytokines. It has been shown that the clinical effects of moxibustion may encompass neural modulation, anti-inflammatory, immunity enhancement, and acceleration effects of the metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Among many of the mechanisms of abdominal obesity, chronic inflammation, cell apoptosis, energy imbalance, and gut microbial enterotypes can result in an excessive accumulation of adipose tissue. [ 35 , 36 ] It is possible that moxibustion treatments could lead to the inhibition of inflammatory, promotion of energy metabolism, and reduction of pro-inflammatory cytokines. It has been shown that the clinical effects of moxibustion may encompass neural modulation, anti-inflammatory, immunity enhancement, and acceleration effects of the metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…One obstacle to broadening the usage of these anthropometric parameters is that the parameters are not always consistent in predicting CVD [16]. A recent study showed that SAD is not more advantageous in predicting metabolic traits than WC, and the study also found that there is gender difference in the correlation between WC, BMI, SAD, and CVD [17]. Previous studies have indicated the essential role of gender in CVD development.…”
Section: Introductionmentioning
confidence: 99%